Analisis Sektor Usaha Kecil & Menengah Menjadi Model Kewirausahaan Sosial Berbasis Ekonomi Kreatif - Dedi Rianto Rahadi (FIRM Journal of Management Studies, 2018)
Social Entrepreneurship is a concept of entrepreneurship (entrepreneurship) that prioritizes socialactivities by empowering the surrounding community. Small and Medium Enterprises (SMEs) can beinvolved to be part of Social-entrepreneurship, to support economic independence of society. Tosupport the sustainability of SMEs as well as a more global reach can be used creative economicapproach of each sector conducted SMEs. It aims to sustain SMEs for a long time and become thefoundation for the Indonesian economy. The purpose of the research is to conduct SME analysis to bepart of social entrepreneuship based on creative economy. Quantitative research methods (descriptivestatistics) and qualitative (interactive analysis models), where data collection is done by observation,in-depth interviews, and approach of PRA (Participatory Rural Appraisal). The results show that localgovernments fully support the existence of SMEs, especially the handicraft sector, by providingfacilities to change policies and funding assistance. Some craftsmen already have the concept of ideasand creativity in improving product quality, it is seen from the innovation of products developed.Society, government and community of artisans support the existence of creative economy-basedsocial entrepreneurship in order to support the improvement of the economy. To support thesustainability of creative entrepreneurial based on creative economy requires the involvement ofgovernment, entrepreneurs, communities through ongoing assistance with policy support siding withSMEs.